Analisis Pengendalian Kualitas Pada Proses Produksi Komponen Kursi Susun Menggunakan Metode SPC(Statistical Process Control) - Abdul Ali Bimansyah; Istantyo Yuwono (Jurnal Sipil Terapan, 2023)
Metalindo Perkasa is a company engaged in the field of furniture that produces chairs. In the production process of stacking chair components, there are problems encountered, namely the number of defects that exceed 1% of the standard determination. It can be a maximum lack of opinion on the company.The research was conducted with the aim of finding solutions to the factors that cause disability and finding action solutions to minimize disability. The method used in this research is Statistical Process Control (SPC). The results showed that the types of defects found were hollow, bent and curly.Factors that cause defects are human factors, machine factors, method factors, action solutions to eliminate defects by training operators, carrying out machine maintenance and checking machine components regularly and increasing supervision when setting degrees.